Participants' accrual and delivery of HIV prevention interventions among men who have sex with men in sub-Saharan Africa: a systematic review - Daniel Nyato; Evodius Kuringe; Mary Drake; Caterina Casalini; Soori Nnko; Amani Shao; Albert Komba; Stefan D. Baral; Mwita Wambura; John Changalucha (BMC, 2018)
Abstract Background Across sub-Saharan Africa (SSA), HIV disproportionately affects men-who-have-sex-with-men (MSM) compared with other men of the same age group in the general population. Access to HIV services remains low among this group although several effective interventions have been documented. It is therefore important to identify what has worked well to increase the reach of HIV services among MSM. Methods We searched MEDLINE, POPLINE and the Web of Science databases to collect published articles reporting HIV interventions among MSM across sub-Saharan Africa. Covidence was used to review the articles. The review protocol was registered in International Prospective Register of Systematic Reviews (PROSPERO) - CRD42017060808. Results The search identified 2627 citations, and following removal of duplicates and inclusion and exclusion criteria, only 15 papers were eligible for inclusion in the review. The articles reported various accrual strategies, namely: respondent driven sampling, known peers identified through hotspot or baseline surveys, engagement with existing community-based organizations, and through peer educators contacting MSM in virtual sites. Some programs, however, combined some of these accrual strategies. Peer-led outreach services were indicated to reach and deliver services to more MSM. A combination of peer outreach and mobile clinics increased uptake of health information and services. Health facilities, especially MSM-friendly facilities attract access and use of services by MSM and retention into care. Conclusions There are various strategies for accrual and delivering services to MSM across SSA. However, each of these strategies have specific strengths and weaknesses necessitating combinations of interventions and integration of the specific context to inform implementation. If the best of intervention content and implementation are used to inform these services, sufficient coverage and impact of HIV prevention and treatment programs for MSM across SSA can be optimized.